Nitrate and Nitrite Treatment Affect Zebrafish Behavior and Brain Metabolomic Profile. (29th May 2020) - Beaver, Laura; García-Jaramillo, Manuel; Truong, Lisa; Axton, Elizabeth; Keller, Rosa; Prater, Mary; Magnusson, Kathy; Tanguay, Robyn; Stevens, Jan; Hord, Norman
Abstract: Objectives: Dietary nitrate contributes to optimal cardiovascular health, exercise performance, and has been hypothesized to improve cognitive performance and affect cerebral blood flow in specific brain regions. While the mechanisms responsible are not fully understood, we tested the hypothesis that nitrate and nitrite treatment would improve indicators of learning and cognitive performance in a zebrafish ( Danio rerio ) model. We also explored the extent to which treatment caused changes in the brain metabolome. Methods: Fish were exposed to sodium nitrate (606.9 mg/L), sodium nitrite (19.5 mg/L), or control water for 2–4 weeks and free swim, startle response, innate predator avoidance, social cohesion, and shuttle box assays were performed. Results: Nitrate and nitrite treatment did not change fish weight, length, predator avoidance, or distance and velocity traveled in an unstressed environment. All treatment groups habituated to a repetitive startle, but nitrate-treated fish moved 10% less distance. Data from the shuttle box learning assay is consistent with a decrease in associative learning or executive function with nitrate and nitrite treatment but, over multiple trials, all treatment groups demonstrated behaviors associated with learning. Nitrate and nitrite-treatment also significantly increased anxiety-like behavior, but did not alter epinephrine, norepinephrine or dopamine levels. Targeted LC-MS/MS analysis revealed no significant increase in brain nitrate or nitrite concentrations with treatment. An untargeted metabolomics analysis found 47 metabolites whose abundance was significantly altered in the brain with nitrate and nitrite treatment including an 18–19% reduction in the neurotransmitter gamma-aminobutyric acid, and 17–22% reduction in its precursor glutamine, which may contribute to the increase anxiety-like behavior in the fish. Conclusions: Nitrate and nitrite treatment did not adversely affect multiple parameters of health but was associated with mild anxiety-like behavior, changes in brain metabolome, and caused a decrease in executive function or associative learning. Funding Sources: Celia Strickland and G. Kenneth Austin III Endowment, the Oregon Agricultural Experimental Station, and National Institutes of Health.